2019
DOI: 10.1186/s12875-019-0907-x
|View full text |Cite
|
Sign up to set email alerts
|

Mixed feelings: general practitioners’ attitudes towards eHealth for stress urinary incontinence - a qualitative study

Abstract: BackgroundStress urinary incontinence (SUI) is the most prevalent subtype of urinary incontinence and is a bothering condition in women. Only a minority of those with SUI consult a general practitioner (GP). EHealth with pelvic floor muscle training (PFMT) is effective in reducing incontinence symptoms and might increase access to care. The role of the GP regarding such an eHealth intervention is unknown. The aim of the study is to gain insight into the attitudes towards a PFMT internet-based, eHealth, interve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 34 publications
1
25
2
Order By: Relevance
“… To provide continuity of care using digital physiotherapy modalities whenever possible. Remote monitoring should be considered, especially for women who were already undergoing physiotherapy treatment of urogynecology and proctological symptoms [ 10 , 11 ]. To discuss with patients the feasibility of performing physiotherapeutic care using digital physiotherapy.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“… To provide continuity of care using digital physiotherapy modalities whenever possible. Remote monitoring should be considered, especially for women who were already undergoing physiotherapy treatment of urogynecology and proctological symptoms [ 10 , 11 ]. To discuss with patients the feasibility of performing physiotherapeutic care using digital physiotherapy.…”
Section: Resultsmentioning
confidence: 99%
“… To inform the patient in advance when recording remote physiotherapy sessions and when recording videos of the body and the posture in general for movement analysis. To align patient expectations with services and be clear in establishing the specific goals, outcomes and indicators for each virtual meeting, so that the patient also feels in control of their health and involved with the treatment [ 10 ]. Recommendations on physiotherapeutic assessment of PFD symptoms and PFM function using telehealth.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…With regard to this latter option, the question remains if the professionals in primary care should be responsible for the uptake of e-Health in their practice. Previous work showed that while GPs support new digital interventions, they also have mixed feelings about their integration into their daily practice, mostly for practical reasons [ 14 , 39 ]. To further support the implementation of e-Health for women with SUI, therefore, its feasibility needs to be systematically evaluated, and technical improvements should be made to the intervention when required and available.…”
Section: Discussionmentioning
confidence: 99%
“…E-Health could be a solution to improve care for women with SUI. Interviews with Dutch GPs by our group showed that GPs consider the use of e-Health with PFMT as a welcome new tool for treating women with SUI [ 14 ]. When interviewed, Dutch women with SUI reported that they expected that e-Health could serve as a tool to bridge obstacles they encountered in regular care, but they underlined they felt the need to also be able to meet with a person during therapy for SUI [ 15 ].…”
Section: Introductionmentioning
confidence: 99%